Compact TCAM: Flow Entry Compaction in TCAM for Power Aware SDN - Kannan, Kalapriya; Banerjee, Subhasis (Distributed Computing and Networking, 2013)
Low latency lookup (typically single cycle) has made Ternary Content Addressable Memory (TCAM) indispensable in high performance network switching devices. However, high power dissipation of TCAM makes it incongruous in switches for today’s power sensitive emerging network framework, viz., Software Defined Network (SDN). In this paper we propose Compact TCAM, an approach that reduces the size of the flow entries in TCAM. We use shorter tags for identifying flows than the original number of bits used to store the flow entries for SDN switches. We leverage the dynamic programming capability of SDN to route the packets using these tags. We show that our approach can be easily implemented using the new SDN framework while optimizing the TCAM space. Our experiments with real world and synthetic traffic show average reduction of TCAM power by 80% in SDN switching devices for a given number of flows.